2021
DOI: 10.3390/su132212467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Factors Affecting Road Traffic Injuries Incidence and Severity in Southern Thailand Based on Accident Investigation Reports

Abstract: Thailand has the second-highest rates of road traffic mortality globally. Detailed information on the combination of human, vehicle, and environmental risks giving rise to each incident is important for addressing risk factors holistically. This paper presents the result of forensic road traffic investigation reports in Thailand and determines risk factor patterns for road traffic injuries. Detailed forensic reports were extracted for 25 serious traffic accident events. The Haddon matrix was used to analyze ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Finally, in Thailand, an in-depth crash investigation study found that 68% of crashes investigated involved speedingmuch higher than expected from police data (Klinjun, Kelly, Praditsathaporn & Petsirasan, 2021).…”
Section: Source 4: Analyses Of Police Based Crash Datamentioning
confidence: 86%
“…Finally, in Thailand, an in-depth crash investigation study found that 68% of crashes investigated involved speedingmuch higher than expected from police data (Klinjun, Kelly, Praditsathaporn & Petsirasan, 2021).…”
Section: Source 4: Analyses Of Police Based Crash Datamentioning
confidence: 86%
“…(GDP) [42,43], and this value is determined by two main factors-the general level of road safety in the country and the level of the average cost of living of the citizens of this country [44]. These two aspects are interconnected by means of risk homeostasis, which is familiar to and accepted by the citizens of the country [45].…”
Section: Methodology For Assessing the Orderliness Of The Process Of The Road Accident Rate Formationmentioning
confidence: 99%
“…Generally speaking, the target function of road safety management is to minimize all types of damage from road accidents, primarily direct damage associated with the death and injury of people in traffic accidents. In general, socio-economic damage in different countries of the world varies in the range from 0.8% to 4% of Gross Domestic Product (GDP) [ 42 , 43 ], and this value is determined by two main factors–the general level of road safety in the country and the level of the average cost of living of the citizens of this country [ 44 ]. These two aspects are interconnected by means of risk homeostasis, which is familiar to and accepted by the citizens of the country [ 45 ].…”
Section: Methodology For Assessing the Orderliness Of The Process Of ...mentioning
confidence: 99%
“…Many researchers have studied the critical factors in crash severity [5][6][7][8] and some focused on the effect of lighting conditions on crash severity [9][10][11][12][13][14][15][16]. Table 1 illustrates a selection of research conducted in this field, making it clear that lighting conditions influence injury severity.…”
Section: Introductionmentioning
confidence: 99%